2018
DOI: 10.1021/acs.estlett.8b00044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Aerosol-Phase State on Secondary Organic Aerosol Formation from the Reactive Uptake of Isoprene-Derived Epoxydiols (IEPOX)

Abstract: Acid-catalyzed reactions between gas-and particle-phase constituents are critical to atmospheric secondary organic aerosol (SOA) formation. The aerosol-phase state is thought to influence the reactive uptake of gas-phase precursors to aerosol particles by altering diffusion rates within particles. However, few experimental studies have explored the precise role of the aerosol-phase state on reactive uptake processes. This laboratory study systematically examines the reactive uptake coefficient (γ) of trans-β-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
267
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(281 citation statements)
references
References 77 publications
14
267
0
Order By: Relevance
“…Thus, the reaction system by Nguyen et al (2011b) can be considered to be closer to the isoprene-H 2 O 2 system. In addition, some other previous studies (Gaston et al, 2014;Riedel et al, 2015;Zhang et al, 2018) showed that RH had a negative effect on the formation of SOA from isoprene-OH systems due to an acid dilution effect. In these studies, acidic sulfate seed particles were used and the acid-catalyzed effect was very obvious.…”
Section: Soa Yieldsmentioning
confidence: 81%
“…Thus, the reaction system by Nguyen et al (2011b) can be considered to be closer to the isoprene-H 2 O 2 system. In addition, some other previous studies (Gaston et al, 2014;Riedel et al, 2015;Zhang et al, 2018) showed that RH had a negative effect on the formation of SOA from isoprene-OH systems due to an acid dilution effect. In these studies, acidic sulfate seed particles were used and the acid-catalyzed effect was very obvious.…”
Section: Soa Yieldsmentioning
confidence: 81%
“…Recent studies have confirmed that organic aerosols, which comprise approximately half of the total submicron aerosol mass in the atmosphere, can change from liquid to glassy state at ambient humidity levels and temperatures (Zobrist et al, 2008;Virtanen et al, 2010;Shrestha et al, 2014;Zhang et al, 2015). The effect of temperature may be especially important when aerosol particles are lifted into the free troposphere, where the temperature change can rapidly alter their phase from liquid to glass .…”
Section: Introductionmentioning
confidence: 99%
“…Kuwata and Martin (2012) showed that the phase state of secondary organic aerosols (SOAs) affects the uptake of ammonia into the particles. Zhang et al (2018) provided experimental and modeling evidence that the reactive uptake of isoprene-derived epoxydiols (IEPOX) into acidic sulfate particles is influenced by the phase state, which can contribute to at least a 30 % reduction in isoprene-derived SOAs in the southeastern USA.…”
Section: Introductionmentioning
confidence: 99%
“…Note that this relation is not accurate for predicting the bulk diffusivity of water and small molecules and it may also underestimate the diffusivity of organic molecules in a highly viscous matrix by a few orders of magnitudes (Champion et al, 2000;Shiraiwa et al, 2011;Power et al, 2013;Marshall et al, 2016;Bastelberger et al, 2017;Reid et al, 2018). The particle phase state, viscosity, and bulk diffusivity have been shown to affect the gas uptake and chemical transformation of organic compounds due to the kinetic limitations of bulk diffusion Abbatt et al, 2012;Zhou et al, 2013;Slade and Knopf, 2014;Arangio et al, 2015;Davies and Wilson, 2015;Wang et al, 2015;Berkemeier et al, 2016;Marshall et al, 2016;Liu et al, 2018;Pratap et al, 2018;Zhang et al, 2018), which may facilitate the long-range transport of organic compounds embedded in viscous or glassy particles (Shrivastava et al, 2017b;Mu et al, 2018). Molecular motion can be hindered in a highly viscous matrix, slowing down photochemical reactions in particles (Lignell et al, 2014;Hinks et al, 2016).…”
Section: Introductionmentioning
confidence: 99%